2011
DOI: 10.1016/j.jde.2011.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Extinction, decay and blow-up for Keller–Segel systems of fast diffusion type

Abstract: We consider the quasi-linear Keller-Segel system of singular type, where the principal part u m represents a fast diffusion like 0 < m < 1. We first construct a global weak solution with small initial data in the scaling invariant norm L N(q−m) 2 for all dimensions N 2 and all exponents q 2. As for the large initial data, we show that there exists a blow-up solution in the case of N = 2. In the second part, the decay property in L r with 1 < r < ∞ for 1 − 2 N m < 1 with the mass conservation is shown. On the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Such systems are widely used to establish different mathematical models describing collective behaviors of organisms and social aggregations, for instance flocks of birds [28], aggregation of bacteria [4], schools of fish [27], swarms formed by insects [5], opinion dynamics [43] and robotics and space missions [36]. Various types of diffusion are considered in these models: While linear diffusion is more commonly used [18], the diffusion can be slow in areas with few particles, known as the degenerate (slow) diffusion model [48]; and similarly, the diffusion can also be fast [47]. One may also consider the nonlocal diffusion, where organisms adopt Lévy process search strategies which have continuous paths interspersed with random jumps [29].…”
Section: Introductionmentioning
confidence: 99%
“…Such systems are widely used to establish different mathematical models describing collective behaviors of organisms and social aggregations, for instance flocks of birds [28], aggregation of bacteria [4], schools of fish [27], swarms formed by insects [5], opinion dynamics [43] and robotics and space missions [36]. Various types of diffusion are considered in these models: While linear diffusion is more commonly used [18], the diffusion can be slow in areas with few particles, known as the degenerate (slow) diffusion model [48]; and similarly, the diffusion can also be fast [47]. One may also consider the nonlocal diffusion, where organisms adopt Lévy process search strategies which have continuous paths interspersed with random jumps [29].…”
Section: Introductionmentioning
confidence: 99%
“…The first result concerned the extinction behavior of solutions for the heat equation with absorption was established in [18]. In recent years, there are many works on the extinction properties of solutions for different kinds of evolution equations (see [3,5,6,13,23,24,26,31] and the references therein). In particular, Li and Wu [20] studied the extinction properties of solutions to the following problem where 0 < m < 1 and k; p > 0, and showed that if p > m, the unique solution with small initial data vanishes in finite time, and if p < m, the maximal solution is positive in X for all t > 0 by using the supersolution and subsolution methods.…”
Section: Introductionmentioning
confidence: 99%
“…The first result concerning the extinction of a solution for the general heat equation with absorption was established in. In recent years, there were many works on the extinction properties of solutions for different kinds of evolution equations (see and the references therein ). In particular, Liu studied the extinction properties of solutions to the following problem with the nonlocal source and absorption {falsenonefalsearrayarrayut=dΔu+ΩuqMathClass-open(x,tMathClass-close)dxkup,arrayMathClass-open(x,tMathClass-close)Ω×MathClass-open(0,MathClass-close),arrayuMathClass-open(x,tMathClass-close)=0,arrayMathClass-open(x,tMathClass-close)∂Ω×MathClass-open(0,MathClass-close),arrayux,0=u0MathClass-open(xMathClass-close),arrayxΩ, where q , p ∈ (0,1), d , k > 0, ΩMathClass-rel⊂double-struckRN(NMathClass-rel≥2), and obtained the critical extinction exponent q = p .…”
Section: Introductionmentioning
confidence: 99%
“…The first result concerning the extinction of a solution for the general heat equation with absorption was established in [11]. In recent years, there were many works on the extinction properties of solutions for different kinds of evolution equations (see [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and the references therein ). In particular, Liu [26] studied the extinction properties of solutions to the following problem with the nonlocal source and absorption 8 <…”
Section: Introductionmentioning
confidence: 99%